PERANCANGAN MULTIMEDIA PEMBELAJARAN MATEMATIKA BERBASIS INQUIRI UNTUK SISWA KELAS IV SEKOLAH DASAR - Madona, Ade Sri; Khairi, Ashabul (IAIN Batusangkar, 2018)
This study aims to produce a learning media design in the form of multimedia mathematics based inquiry learning for fourth grade students of elementary school. This type of research is development research using the 4D model. This study looks at how the procedures for developing multimedia learning mathematics learning are viewed from the form of flowcharts, Storyboarding, and multimedia programming results of mathematics learning. Then validation was seen from 3 aspects including the content aspect, constructive aspects and language aspects. From the results of the research that has been carried out obtained the average validation of 84.5 with a very valid category. Based on the research data that has been obtained, it can be concluded that the multimedia learning mathematics based inquiry has been valit and can be used in learning in elementary school.